Implementation of Effective Communication as an Effort to Improve The Quality of Service in North Sumatra University Dental and Oral Hospital - Jan Terrie; Muhammad Yunus (Cakradonya Dental Journal, 2023)
Communication is the most important aspect of collaboration between professionals consisting of doctors, nurses, pharmacists, medical records, and patients. In fact, 7080% of errors in health services are caused by poor communication and a lack of understanding between team members or between professionals. Lack of communication can also cause delays in serving patients and errors in handling patients. One of the ways to provide Effective Communication training is through using the Situation Background Assessment Recommendation (SBAR) method. The purpose of this study was to create and correct effective communication to improve service quality and patient safety at the Dental and Oral Hospital of North Sumatra University. The research method used a qualitative approach, and the informants were all the staff or employees at the Dental and Oral Hospital of North Sumatra University. Methods of data collection were carried out by direct observation and giving questionnaires before and after the communication training. The changes observed or measured in the research were before and after the SBAR training, that is the increase and the change in the behaviour of the officers. The result of this study shows that respondents had fairly good percentage results, with knowledge of 73.65% and applying effective communication with the SBAR method of 57.49%. Concluded that Therefore, effective communication is one of the indicators for monitoring hospital quality and patient safety.